2016
DOI: 10.1590/1678-457x.6674
|View full text |Cite
|
Sign up to set email alerts
|

Maize flour parameters that are related to the consumer perceived quality of ‘broa’ specialty bread

Abstract: A wide range of quality parameters have been used to describe maize flours for food use, but there is no general agreement about the most suitable parameters for breadmaking. The objective of this study was to identify the maize flour parameters related to the consumer perceived quality of Portuguese broa bread (more than 50% maize flour). The influence of eleven maize landraces was assessed and compared with commercial flour using baking tests. The broa were evaluated by instrumental (colour, firmness) and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 21 publications
3
24
1
1
Order By: Relevance
“…An important aspect of both the Amiúdo and Castro Verde populations is the fact that their flours can be used for food. In fact, a recent sensory hedonic analysis of maize bread, including bread obtained from these populations, showed that both populations were able to produce bread with preferential characteristics (Carbas et al., ). With the objective of integrating these two populations in a quality‐oriented breeding program in due course, several traits related to consumer preferences and technological, nutritional, and organoleptic properties (quality traits) were measured.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An important aspect of both the Amiúdo and Castro Verde populations is the fact that their flours can be used for food. In fact, a recent sensory hedonic analysis of maize bread, including bread obtained from these populations, showed that both populations were able to produce bread with preferential characteristics (Carbas et al., ). With the objective of integrating these two populations in a quality‐oriented breeding program in due course, several traits related to consumer preferences and technological, nutritional, and organoleptic properties (quality traits) were measured.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of both the Amiúdo and Castro Verde populations is the fact that their flours can be used for food. In fact, a recent sensory hedonic analysis of maize bread, including bread obtained from these populations, showed that both populations were able to produce bread with preferential characteristics (Carbas et al, 2016).…”
Section: Implications For a Quality-oriented Breeding Programmentioning
confidence: 99%
See 3 more Smart Citations